Management System for Large Li-Ion Battery Packs with a New Adaptive Multistage Charging Method - Velho, Ricardo (2019)
Submitted by CALADO (rc@ubi.pt) on 2019-05-02T13:37:21Z No. of bitstreams: 1 6.2.34_Energies_2017.pdf: 15811443 bytes, checksum: d762d650063208e6a977c5d7b38523dc (MD5)